Analysis of The Reliability of The 20kV Distribution System of PT PLN (Persero) ULP Tarakan Using Root Cause Problem Solving Methods - Sukmawati; Budiman, Achmad (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2023)
The distribution system is one of the components of the power system that cannot be separated from the occurrence of interference or damage, which causes factors from within the equipment and factors from outside that can cause blackouts. In this final project, the reliability problems of SAIDI, SAIFI and CAIDI in 2021 at PT PLN (Persero) ULP Tarakan will be discussed using the RCPS (Root Cause Problem Solving) method. The parameters used to see the reliability of the distribution network are SAIDI (System Average Interruption Duration Index), SAIFI (System Average Interruption Frequency Index) and CAIDI (Customer Average Interruption Duration Index). By comparing the SAIDI, SAIFI and CAIDI reliability indices with the IEEE 1366-2003, SPLN 68-2: 1986 and WCS&WCC reliability indices. Where the comparison results of SPLN 68-2: 1986 and SAIDI = 21.09 j/p/t and 6.45 j/p/t (Meets Standard), SPLN 68-2: 1986 and SAIFI = 3.2 k/p/t and 7.38 k/p/t (Does Not Meet Standard), IEEE 1366-2003 and SAIDI = 2.3 j/p/t (Does Not Meet Standard), IEEE 1366-2003 and SAIFI = 1.45 k/p/t and 7.38 k/p/t (Does Not Meet Standard), IEEE 1366-2003 and CAIDI = 1.47 j/g/t and 9.89 j/g/t (Does Not Meet Standard), WCS&WCC and SAIDI = 3 j/p/t and 6.45 j/p/t (Does Not Meet Standard), WCS&WCC and SAIFI = 1.666 k/p/t and 7.38 k/p/t (Does Not Meet Standard). If it does not meet the predetermined standards, Root Cause Problem Solving analysis is carried out.